Speaking English Speaking Skills Through Collaborative Learning: Literature Review - Tindaon, Cinta Yulistra; Napitupulu, Selviana (Innovative: Journal Of Social Science Research, 2025)
This study investigates the evolution of English language skills through the use of collaborative learning. This approach encourages collaboration among students through communication-based exercises such as role-playing, group discussions, and presentations. According to the literature, students' confidence, fluency, and courage in speaking English are all effectively improved through collaborative learning. In addition, this method fosters a dynamic, engaging, and life-relevant learning environment. Therefore, collaborative learning can offer a way to overcome the challenges in teaching English language skills.